1982
DOI: 10.1128/aem.43.4.740-746.1982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cell lines and immunofluorescence and plaque assay procedures for quantifying reoviruses in sewage

Abstract: Twelve continuous cell lines were tested to determine their sensitivity to reovirus types 1, 2, and 3 isolated from sewage. Madin-Darby bovine kidney (MDBK), rhesus monkey kidney (LLC-MK2), and human embryonic intestinal (intestinal 407) cells were most sensitive, respectively. In a similar study, MDBK cells were more sensitive than LLC-MK2 and Buffalo green monkey kidney (BGM) cells to sewage-isolated, protamine-precipitated reoviruses which had not been serotyped and had no previous cell contact. Sewage-isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…The viruses were prepared in Buffalo green monkey (BGM) kidney cells. The BGM cells between passages 130-150 were grown until they became a confluent monolayer by using Eagle's minimum essential medium with Hanks salts (Sigma, St. Louis, Mo., U.S.A.) and Leibovitz's L-15 medium (Gibco BRL, Grand Island, N.Y., U.S.A.), penicillin-streptomycin (100 U/ml and 100 µg/ml, respectively), and 9 mM NaHCO 3 at 37 C and 5% CO 2 (19).…”
Section: Methodsmentioning
confidence: 99%
“…The viruses were prepared in Buffalo green monkey (BGM) kidney cells. The BGM cells between passages 130-150 were grown until they became a confluent monolayer by using Eagle's minimum essential medium with Hanks salts (Sigma, St. Louis, Mo., U.S.A.) and Leibovitz's L-15 medium (Gibco BRL, Grand Island, N.Y., U.S.A.), penicillin-streptomycin (100 U/ml and 100 µg/ml, respectively), and 9 mM NaHCO 3 at 37 C and 5% CO 2 (19).…”
Section: Methodsmentioning
confidence: 99%
“…Smith and Gerba (1982) have shown that as few as 10 infectious units per liter can be reliably detected by IFA within less than 24 h incubation. Ridinger et al (1982) found that IFA is more sensitive and more rapid than the plaque assay for the detection of reoviruses. Reoviruses in excess of 10 4 per liter of raw sewage were detected by IFA.…”
Section: Fluorescence Microscopy and Virus Infectivitymentioning
confidence: 98%
“…This method uses virus-specific antibody labelled with a fluorescent dye to visualize cell-associated viral antigens (Jeffery and Aarons, 2009). The use of the IFAs has been described previously for detecting infectious rotaviruses in sewage (Ridinger et al, 1982;Smith and Gerba, 1982). Smith and Gerba (1982) have shown that as few as 10 infectious units per liter can be reliably detected by IFA within less than 24 h incubation.…”
Section: Fluorescence Microscopy and Virus Infectivitymentioning
confidence: 99%
“…Reovirus (respiratory enteric orphan virus) is a member of the Reoviridae family. Reovirus is ubiquitous and has been isolated from untreated sewage, stagnant water and rivers throughout the world [21,22]. As the name suggests, reovirus infects the respiratory and gastrointestinal tract but is not associated with a named human disease, although it can infrequently cause flu-like upper respiratory tract symptoms or a mild diarrhoeal illness.…”
Section: Oncolytic Reovirus As An Archetype For Clinical Developmentmentioning
confidence: 99%